Influence of Molecular Orbitals on Magnetic Properties of FeO2Hx - Alexey O. Shorikov; Sergey L. Skornyakov; Vladimir I. Anisimov; Sergey V. Streltsov; Alexander I. Poteryaev (Molecules, 2020)
Recent discoveries of various novel iron oxides and hydrides, which become stable at very high pressure and temperature, are extremely important for geoscience. In this paper, we report the results of an investigation on the electronic structure and magnetic properties of the hydride FeO <semantics> 2 </semantics> H <semantics> x </semantics> , using density functional theory plus dynamical mean-field theory (DFT+DMFT) calculations. An increase in the hydrogen concentration resulted in the destruction of dimeric oxygen pairs and, hence, a specific band structure of FeO <semantics> 2 </semantics> with strongly hybridized Fe- <semantics> t 2 g </semantics> -O- <semantics> p z </semantics> anti-bonding molecular orbitals, which led to a metallic state with the Fe ions at nearly 3+. Increasing the H concentration resulted in effective mass enhancement growth which indicated an increase in the magnetic moment localization. The calculated static momentum-resolved spin susceptibility demonstrated that an incommensurate antiferromagnetic (AFM) order was expected for FeO <semantics> 2 </semantics> , whereas strong ferromagnetic (FM) fluctuations were observed for FeO <semantics> 2 </semantics> H.